2019
DOI: 10.1038/s41598-019-51390-8
|View full text |Cite
|
Sign up to set email alerts
|

Towards genomic database of Alexander disease to identify variations modifying disease phenotype

Abstract: Alexander disease (AxD) is an extremely rare neurodegenerative disorder caused by glial fibrillary acidic protein (GFAP) gene mutations. Compared with the cerebral type, which is characterized by infantile onset, the bulbospinal type and intermediate form are associated with a late onset, spanning from juveniles to the elderly, and more diverse clinical spectrum, suggesting the existence of factors contributing to phenotypic diversity. To build a foundation for future genetic studies of this rare disease, we o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
5
0
2
Order By: Relevance
“…Consistent with these previous reports, increases were detected in proteins associated with reactive astrocytes (Gfap, Vim, Cd44) ( 23 ), RFs (Cryab, Rps27a, Hsp27 (also known as Hspb1), Ddx3x, Ccnd2, Rack1) ( 22 , 33 , 34 ), and autophagy (Sqstm1) ( 35 ). Gan, which targets Gfap for proteasomal degradation ( 36 ), was also elevated and has gene variants correlated with the age of clinical onset in AxD patients ( 37 ). Heightened levels of Stat3 were also detected in GFAP Tg ; Gfap +/ R236H mice, a phosphorylated transcription factor activated in reactive gliosis ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with these previous reports, increases were detected in proteins associated with reactive astrocytes (Gfap, Vim, Cd44) ( 23 ), RFs (Cryab, Rps27a, Hsp27 (also known as Hspb1), Ddx3x, Ccnd2, Rack1) ( 22 , 33 , 34 ), and autophagy (Sqstm1) ( 35 ). Gan, which targets Gfap for proteasomal degradation ( 36 ), was also elevated and has gene variants correlated with the age of clinical onset in AxD patients ( 37 ). Heightened levels of Stat3 were also detected in GFAP Tg ; Gfap +/ R236H mice, a phosphorylated transcription factor activated in reactive gliosis ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many pathogenic mutations have been reported in AxD, Majority of them is point mutation and indels. (Quinlan, Brenner, Goldman, & Messing, 2007;Yasuda et al, 2019) Alexander disease is considered a gain-of function disorder in the sense that the GFAP mutations produce consequences that differ dramatically from those caused by the absence of GFAP (like that case in this study).Although the main cause of sever and lethal AxD is accumulation of toxic defective proteins in astrocytes as a consequence of point mutation in GFAP gene; but, in this case with deletion of 1-9 exons, GFAP protein is produced from intact allele with less than 50% performance-This phenomenon is called haploinsufficiencybesides, previous studies demonstrated that deletion of some exons like exon 5. (Green, 2018) After a pathogenic mutation is discovered, it is preferred to assess mutation in other family members, whom could be asymptomatic or minimally affected.…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact that bulbospinal ALXDRD, which is more common in adulthood, shows a milder phenotype and slower progression than cerebral ALXDRD, which is more common in infancy [1], it is logical to speculate that the low number of reports of older‐adult‐onset ALXDRD may be due to their milder phenotype with slower progression or asymptomatic status. Furthermore, even among bulbospinal ALXDRD cases, older‐age‐at‐onset cases (≥45 years old) tend to show a more severe phenotype than younger‐age‐at‐onset cases (<45 years old) [21]. Therefore, to assess the association between disease progression and severity depending on the age at onset, we compared older‐adult‐onset cases with younger‐adult‐onset cases, as control cases, whose clinical classification and period from onset to diagnosis were matched.…”
Section: Discussionmentioning
confidence: 99%
“…In ALXDRD, the younger the onset age, the more severe the clinical phenotype tends to be [1,21]. Thus, we hypothesized that older-adult-onset ALXDRD would be associated with a much milder phenotype than younger-adult-onset ALXDRD.…”
Section: Me Thodsmentioning
confidence: 99%